Research data management at the University of Bristol: Charting a course from project to service. Issue 4 (1st September 2015) - Hiom, Debra; Fripp, Dom; Gray, Stephen; Snow, Kellie; Steer, Damian
Abstract : Purpose: – The purpose of this paper is to chart the development of research data management services within the University of Bristol, from the initial Jisc-funded project, through to pilot service and planned core funding of the service. Design/methodology/approach: – The paper provides a case study of the approach of the University of Bristol Library service to develop a sustainable Research Data Service. Findings: – It outlines the services developed during the project and pilot phases of the service. In particular it focuses on the sustainability planning to ensure that research data management is embedded as a core university service. Originality/value: – The case study provides practical advice and valuable insights into the issues and experiences of ensuring that research data management is properly valued and supported within universities.